Workshop Self-Balanced Scorecard untuk Pengelolaan Human Capital Mahasiswa Universitas Djuanda - Nizmah Chalifah; Eka Taruna Putra; Roby sampai; Muhammad Rifai; Waska Warta (LOSARI DIGITAL, 2026)
Education is a strategic investment that plays an important role in improving the quality of human resources and future competitiveness. However, many students still lack understanding regarding how to manage educational investment systematically and sustainably. This community service program aimed to improve students’ understanding of human capital management through the implementation of the Self-Balanced Scorecard approach at Universitas Djuanda. The activities were conducted using participatory methods, including observation, training, workshops, mentoring, and evaluation. Participants were introduced to four major perspectives of the self-balanced scorecard consisting of academic, self-development, social-spiritual, and career-financial perspectives. The evaluation results showed that 95% of participants considered the Self-Balanced Scorecard relevant to their needs, 94% reported a better understanding of educational investment, 96% perceived significant benefits for self-development, and 97% expressed interest in participating in similar future activities. Participants were also able to formulate measurable personal development indicators and strategic self-improvement plans. The implementation of the program contributed positively to strengthening students’ motivation, self-management skills, and long-term educational orientation.